Ways of informing parents of children with celiac disease about the disease and gluten-free nutrition - Stojanović-Jovanović Biljana; Jovanović Stevan; Vuletić Biljana (Association of Nurses Technicians and Midwives, 2021)
Introduction: Celiac disease is an autoimmune disease caused by an inadequate immune response in contact with gluten in genetically predisposed individuals. Barriers to maintaining a strict gluten-free diet arise due to several factors, the most common of which are: inadequate information, insufficient education about the disease, food contamination. Aim of the research: To determine the ways of informing parents about the celiac disease that has been diagnosed in their children, as well as to learn about the necessary procedures to improve information about gluten-free diet. Subjects and method: The study included a sample of 116 parents whose children are diagnosed with celiac disease and who are on a gluten-free diet. The place of research is the Institute for Maternal and Child Health of Serbia "Dr Vukan Cupic" in New Belgrade and the University Children's Clinic in Belgrade. The research instrument used is the Questionnaire on Parents' Awareness of Celiac Disease, which was created for the purposes of this research. Results with discussion: The results of the study show that 47.14% of parents of children with celiac disease ask for information about the proper nutrition of their children and gluten-free foods from the doctor of the institution where the child was diagnosed with the disease. In order to better understand the diagnosis of celiac disease in their child, 53.01% of parents most often chose to talk to the doctor who treats the child. Conclusion: Information on proper nutrition of children and gluten-free foods, as well as specific information on celiac disease, is requested from the doctor of the institution where the disease was diagnosed in the child and where they go for check-ups. Many complications caused by unrecognized celiac disease could be prevented by timely diagnosis and proper posture of the child, which contributes to good and adequate information.